(3eaghegG(B- (3eeGQSGJgG GdESJQGJjLjI(B- (3OhQgG aj JfajP GSJQGJjLjI GdefXeIs - (3YHO GdMcje(B, (3bGVjs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2023)
(3YGdL gGPG GdcJGH GdEOGQI GdESJQGJjLjI ddehGQO GdHTQjI ef NdGd GdEWGQ GdfXQj GdeJVef eGgjI heaghe EOGQI GdehGQO GdHTQjI, GdJWhQ GdJGQjNj dgG, CgOGagG hJMOjGJgG, GdEOGQI GdESJQGJjLjI ddehGQO GdHTQjI feGPLgG hCfeGWgG hcPG JUejegG hJfajPgG , HGdEVGaI Edi eaghe hCfhGY eeGQSGJ GdEOGQI GdESJQGJjLjI ddehGQO GdHTQjI , JUejegG hJWHjbgG , GdQbGHI Ydi GSJQGJjLjGJ JWhjQ GdehGQO GdHTQjI heJGHYI JWHjbgG, hOhQ GdEOGQI GdGSJQGJjLjI ddehGQO GdHTQjI aj JfajP GSJQGJjLjI GdefXeI(B. s
(3eQGLY U(B.175s
Keywords: (3GdEOGQI GdGSJQGJjLjIs; (3GdehGQO GdHTQjIs